Polymineralic Inclusions in Loparite-(Ce) from the Lovozero Alkaline Massif (Kola Peninsula, Russia): Hydrothermal Association in Miniature - Julia A. Mikhailova; Yakov A. Pakhomovsky; Ekaterina A. Selivanova; Alena A. Kompanchenko (Minerals, 2023)
Polymineralic inclusions in loparite-(Ce) in alkaline rocks from the Lovozero massif (Russia) were investigated using electron microprobe analysis, Raman spectroscopy, and X-ray diffraction. A total of 21 mineral species and two groups of minerals (pyrochlore- and labuntsovite-group minerals) were found in these inclusions. Minerals in loparite-hosted inclusions can be divided into two groups: (1) minerals found typically in rocks bearing loparite-(Ce) grains (groundmass minerals) such as aegirine, magnesio-arfvedsonite, potassic feldspar, albite, fluorapatite, etc.; and (2) minerals that were not found in the rock outside of the loparite-(Ce) grains. The latter include lorenzenite, labuntsovite-group minerals, minerals of the neptunite–manganoneptunite series, vinogradovite, catapleiite, fluorite, britholite-(Ce), barylite, genthelvite, and barite, found in the studied samples exclusively inside loparite-(Ce) crystals. The minerals of the second group are typical hydrothermal minerals. We assume that the skeletal crystals of loparite-(Ce), when growing, captured both co-crystallizing minerals and small drops of the mineral-forming solution. Such drops subsequently crystallized within the loparite-(Ce), resulting in the formation of a hydrothermal mineral association.